2018
DOI: 10.1038/s41598-017-19077-0
|View full text |Cite
|
Sign up to set email alerts
|

Surround inhibition can instantly be modulated by changing the attentional focus

Abstract: To further investigate the mechanism of surround inhibition (SI) and to determine whether adopting different attentional strategies might have an impact on the modulation of SI, the effects of adopting an external (EF) or internal focus of attention (IF) on SI and motor performance were investigated. While performing an index flexion with either an EF or IF, transcranial magnetic stimulation was applied at various time points in 14 healthy subjects. When adopting an EF compared to an IF, the results show an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 46 publications
(72 reference statements)
4
40
0
2
Order By: Relevance
“…In line with this proposal, it has been shown that isometric contractions can be maintained longer when an external focus of attention is adopted (Kuhn et al, 2017a). Interestingly, this improvement of performance was accompanied by an increase in SICI (Kuhn et al, 2017a; Kuhn et al, 2017b) and an increase in surround inhibition (Kuhn et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this proposal, it has been shown that isometric contractions can be maintained longer when an external focus of attention is adopted (Kuhn et al, 2017a). Interestingly, this improvement of performance was accompanied by an increase in SICI (Kuhn et al, 2017a; Kuhn et al, 2017b) and an increase in surround inhibition (Kuhn et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…115 Additionally, engaging in EF increases time to failure, reduces ratings of perceived exertion, 116,117 and increases movement efficiency potentially by reducing unnecessary muscle contributions by modulating the inhibitory mechanisms within the primary motor cortex. 117,118…”
Section: Modified External Focus Of Attention For Visuospatial Attentionmentioning
confidence: 99%
“…For example, it has been reported that attentional focus (external versus internal) modulates MEPs evoked by motor cortex stimulation (Kuhn et al 2018). Concurrent leg muscle activation results in a prolonged attenuation of EMG activity (i.e.…”
Section: Discussionmentioning
confidence: 99%